2006
DOI: 10.1007/s10582-006-0306-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the change of the electron saturation current of a dc-heated emissive probe

Abstract: We report on experimental investigations of the change of the electron saturation current of a dc-heated emissive probe with the probe heating current. According to the simple theory of the emissive probe, the electron saturation current should not be affected by emission. However, in many experiments a variation of the electron saturation current with the emission current was observed. We consider two possible reasons for such variations: (a) the influence of the space charge around the probe shaft, (b) the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…This dependence of I co (T p ) with the wire temperature T p in Fig. 1 has been previously reported by different authors but has not received a fully satisfactory explanation yet [14]. As proposed in [10], Fig.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…This dependence of I co (T p ) with the wire temperature T p in Fig. 1 has been previously reported by different authors but has not received a fully satisfactory explanation yet [14]. As proposed in [10], Fig.…”
Section: Resultssupporting
confidence: 49%
“…We have concluded that V p \ could be determined by using hot emissive Langmuir probes plotting V F (T P ) as a function of T p (or equivalently, probe heating current In) as discussed in [8]- [10] and [14]. The abrupt change in the slope of V F (T P ) that appears at temperature T ph where V F (T pl ) ~ V ph determines the value of the plasma potential.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[1][2][3]5]. This wire is heated up to the electron thermoionic emission using a DC current and is electrically biased as the collecting probes.…”
Section: Introductionmentioning
confidence: 99%
“…For large enough wire temperatures this emitted electron current produces a steeper transition in the IV curve. Then, this transition from electron emission to collection creates an abrupt jump in I p (V p ) that allows an accurate determination of the plasma potential V sp , currently determined from the IV curves by means of either, the floating point or the inflection point methods [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%